1964
DOI: 10.1111/j.1423-0410.1964.tb03308.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Strength on the Serologic Behavior of Red Cell Isoantibodies*

Abstract: Summary The effect of a low ionic strength environment on the serologic activity of 64 anti‐sera was studied by substituting iso‐osmotic glycine for buffer in the diluent. Some enhancement was achieved with most antibodies, both complete and incomplete, except for antibodies with ABO and Lewis specificity. Red cell sensitization and possibly agglutination of sensitized cells appear to be enhanced in the presence of a low ionic strength milieu. A reduction of ionic strength from 0.26 to about 0.07 results in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1965
1965
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Isotonic saline (0.15 M) is generally used for blood grouping purposes, but it is well known that the rate of the reaction between polyclonal IgG antibodies and anti gen is increased by a reduction of ionic strength from 0.15 to 0.03 M [19,20]. The reaction between purified polyclonal IgM anti-A and A red cells, on the other hand, is not increased in media of low ionic strength [21], The mechanism of changed association rates in media with different ionic strengths is not known and either antigen or antibody could be affected.…”
Section: Discussionmentioning
confidence: 99%
“…Isotonic saline (0.15 M) is generally used for blood grouping purposes, but it is well known that the rate of the reaction between polyclonal IgG antibodies and anti gen is increased by a reduction of ionic strength from 0.15 to 0.03 M [19,20]. The reaction between purified polyclonal IgM anti-A and A red cells, on the other hand, is not increased in media of low ionic strength [21], The mechanism of changed association rates in media with different ionic strengths is not known and either antigen or antibody could be affected.…”
Section: Discussionmentioning
confidence: 99%
“…Pirofsky [7a,7 b] has shown that non-antibody gammaglobulin is adsorbed onto the surface of human red cells and that such cells do not give a positive antiglobulin test, and recently it has been de monstrated that at very low salt concentration non-antibody gamma globulin is bound to the red cell surface and gives a positive anti globulin test [3]. It follows that both antibody-and non-antibodygammaglobulin can give positive and negative antiglobulin reactions.…”
Section: Reaction Patterns Of Dn Cellsmentioning
confidence: 99%
“…Two possible modes of action are advanced to explain this observation: 1. the proteolytic property of the enzyme removes material from the surface of the red cell, thus exposing additional antigen [16,18,20], and 2. the enzyme modifies the ionic strength at the site of reaction between the red cell and antibody and leads to increased binding of antibody [8,15,19]. Hughes-Jones et al [12,13] have shown that the treatment of erythrocytes with ficin causes an increase in the value of the equi librium constant as a result of more rapid union of antigen and anti body.…”
mentioning
confidence: 99%